2008
DOI: 10.1007/s10529-008-9896-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus sphaericus Mtx1 and Mtx2 toxins co-expressed in Escherichia coli are synergistic against Aedes aegypti larvae

Abstract: Mtx1 and Mtx2 are mosquitocidal toxins produced by some strains of Bacillus sphaericus during vegetative phase of growth. Mtx1 from B. sphaericus 2297 shows higher toxicity against Culex quinquefasciatus larvae than to Aedes aegypti larvae whereas Mtx2 from B. sphaericus 2297 shows lower toxicity against C. quinquefasciatus than to A. aegypti larvae. To test synergism of these toxins against A. aegypti larvae, mtx1 and mtx2 genes were cloned into a single plasmid and expressed in Escherichia coli. Cells produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Although S-layer and Mtx toxins have shown entomopathogenic activity [16, 18], these do not have the properties of a biological controller. Meanwhile, the vegetative cells of L. sphaericus can persist and recycle in the environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although S-layer and Mtx toxins have shown entomopathogenic activity [16, 18], these do not have the properties of a biological controller. Meanwhile, the vegetative cells of L. sphaericus can persist and recycle in the environment.…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant Mtx toxins and S-layer protein have been assessed against Ae. aegypti larvae [16, 18], but there are no reports regarding the whole vegetative cell. Recent genomic studies have revealed that some L. sphaericus strains have hemolysins and chitinases genes, which could play an important role in the entomopathogenic activity of these strains [1921].…”
Section: Introductionmentioning
confidence: 99%
“…Both the vegetative toxins Mtx1 and Mtx2 are able to act in synergism against Aedes aegypti (Rungrod et al, 2009) and each acts synergistically with the Bin toxin (Wirth et al, 2007) and may be valuable in enhancing the effectiveness of L. sphaericus spore preparations. Although the Mtx proteins are produced during vegetative growth and Bin proteins are associated with the spores, it has been shown that, in intoxicated insects, most L. sphaericus have entered vegetative growth by the time that the larvae die (Charles, 1987).…”
Section: Toxin Synergymentioning
confidence: 99%
“…These are (1) the binary toxin (Bin) composed of two proteins of 42 kDa (BinA) and 51 kDa (BinB), which are synthesized during sporulation and co-crystallize, (2) the soluble mosquitocidal toxins (Mtx1, Mtx2 and Mtx3) produced during vegetative growth and (3) the two-component crystal toxin (Cry48Aa1/Cry49Aa1). Rungrod et al (2009) reported the synergistic activity of Mtx1 and Mtx2 toxins against A. aegypti (Diptera: Culicidae) larvae. Jones et al (2008) reported the highly restricted target specificity of the Cry48Aa-Cry49Aa binary toxin from B. sphaericus towards C. quinquefasciatus mosquito larvae (Diptera: Culicidae) with non-toxicity to Coleopteran, Lepidopteran and other Dipteran insects including closely related Aedes and Anopheles mosquitoes.…”
Section: Bacillus Sphaericus Based Biopesticide: Potential Effect In mentioning
confidence: 99%